Introduction to Diplodocoidea - van der Linden, Tom (2025)
Diplodocoidea is one of the most iconic clades of the giant sauropod dinosaurs,known for their elongated necks and tails, and distinctive skull morphology. This group,existing from the Middle Jurassic to the early Late Cretaceous, encompasses threemain families: Rebbachisauridae, Dicraeosauridae, and Diplodocidae. These sauropodswere globally distributed, demonstrating significant diversity in body plans, feedingstrategies, and ecological niches. Diplodocoid paleontology has been marked byextensive studies focusing on skeletal morphology, biomechanics, histology, and evolutionaryrelationships. Significant research has also explored their ontogeny and nichepartitioning, suggesting that diplodocoids had specialized adaptations for low- to midlevelbrowsing. This contribution is the introduction to a special volume that aims tosynthesize current research on Diplodocoidea, offering insights into their evolutionarysuccess, with subsequent contributions addressing their phylogenetic relationships,ontogeny, and morphological variation.